Muhammadiyah Sebagai Pelopor Gerakan Sosial dan Pendidikan di Indonesia - Alya Aqilla; Putri Nailah Azahra; Rini Febrianti; Dhio Gonzales; Wismanto Wismanto; Wira Ramashar (Jurnal Budi Pekerti Agama Islam, 2025)
Muhammadiyah, which was founded in 1912, has played a pioneering role in social and educational movements in Indonesia. This article examines Muhammadiyah's contribution to improving the quality of life of the community through various educational programs and social initiatives. Research shows that Muhammadiyah has established more than 17,000 educational institutions that provide access to quality education, as well as implementing community empowerment programs that encourage economic independence. In addition, Muhammadiyah is active in social activities, including disaster management and human rights advocacy, which shows the organization's commitment to social justice. Through a holistic approach to education that prioritizes character and leadership development, Muhammadiyah seeks to form a young generation that cares about society. The aim of this research is to reveal Muhammadiyah's role in improving the quality of life of the Indonesian people through the educational programs and social initiatives it carries out. This research method uses a qualitative method with a descriptive approach to examine the role of Muhammadiyah in social movements and education in Indonesia. The research results show that Muhammadiyah not only functions as a religious organization, but also as an agent of change that contributes to creating a more prosperous and just society in Indonesia.